A study on the extraoral infraorbital nerve block - Ventanilla, III Oscar D.
This preliminary study was conducted to determine the value of the extroral infraorbital nerve block in clinical practice. To accomplish this, effectivity and ease of administration were verified, onset and duration were determined, and the degree of traumatism assessed. Test results showed that the technique was effective easy to administer, and atraumatic. With only 1m1 of solution, the onset of profound anesthesia ranged from 0-2 minutes after withdrawal of the needle, and its effects lasted to well over an hour and a half.